Up-Regulated Expression of Extracellular Matrix Remodeling Genes in Phagocytically Challenged Trabecular Meshwork Cells - Porter, Kristine M.; Epstein, David L.; Liton, Paloma B. (PLOS ONE, 2012)
Background Cells in the trabecular meshwork (TM), the tissue responsible for draining aqueous humor out of the eye, are known to be highly phagocytic. Phagocytic function in TM cells is thought to play an important role in the normal functioning of the outflow pathway. Dysfunction of phagocytosis could lead to abnormalities of outflow resistance and increased intraocular pressure (IOP). However, the molecular mechanisms triggered by phagocytosis in TM cells are completely unknown. Methodology/Principal Findings Gene expression profile analysis of human TM cells phagocytically challenged to E. coli or pigment under physiological and oxidative stress environment were performed using Affymetrix U133 plus 2.0 array and analyzed with Genespring GX. Despite the differential biological response elicited by E. coli and pigment particles, a number of genes, including MMP1, MMP3, TNFSF11, DIO2, KYNU, and KCCN2 showed differential expression with both phagocytic ligands in all conditions. Data was confirmed by qPCR in both human and porcine TM cells. Metacore pathway analysis and the usage of recombinant adenovirus encoding the dominant negative mutant of IkB identified NF-κB as a transcription factor mediating the up-regulation of at least MMP1 and MMP3 in TM cells with phagocytosis. In-gel zymography demonstrated increased collagenolytic and caseinolytic activities in the culture media of TM cells challenge to E. coli. In addition, collagenolytic I activity was further confirmed using the self-quenched fluorescent substrate DQ-Collagen I. Conclusions/Significance Here we report for the first time the differential gene expression profile of TM cells phagocytically challenged with either E. coli or pigment. Our data indicate a potential role of phagocytosis in outflow pathway tissue homeostasis through the up-regulation and/or proteolytic activation of extracellular matrix remodeling genes.